THE IDEOLOGICAL PROCESSES: HISTORICAL AND PHILOSOPHICAL ANALYSIS - Ziyoitdinovich, Sharipov Abduhakimjon (The journal of contemporary issues in business and government, 2021)
The following article analyzes the ideological processes, randomizes the history of ideological thought, their application in the life of society, sustainable development in line with the Strategy of Actions of the new national development of Uzbekistan, which serves to raise the morale of the international community, sustainable development and the conceptual principles of the idea of national ascent, aimed at educating young generation who can make an invaluable contribution to their worthy place in the world, from a socio-philosophical point of view. As a result, these analyzes serve to increase the effectiveness and efficiency of spiritual-enlightenment work and to turn creativity into a nationwide movement, strengthening the sense of involvement in the ongoing reforms in the hearts of young generation, transform a healthy weltanschauung and creativity into a nationwide movement through the widespread promotion of the idea of “From national revival to national progress” which is based on the principles of goodness and humanity.